Exploring mathematics anxiety and attitude: Mathematics students’ experiences - Sahri, Nurul Ashikin; Wan Kamaruzaman, Wan Nur Farahdalila; Mohd Jamil, Jastini; Mohd Shaharanee, Izwan Nizal (IP Publishing LLC, 2017)
A quantitative and correlational, survey methods were used to investigate the relationships among mathematical anxiety and attitude toward student’s mathematics performance. Participants were 100 students volunteer to enroll in undergraduate Industrial Statistics, Decision Sciences and Business Mathematics at one of northern university in Malaysia. Survey data consisted of demographic items and Likert scale items. The collected data was analyzed by using the idea of correlation and regression analysis. The results indicated that there was a significant positive relationship between students’ attitude and mathematics anxiety. Results also indicated that a substantial positive effect of students’ attitude and mathematics anxiety in students’ achievement. Further study can be conducted on how mathematical anxiety and attitude toward mathematics affects can be used to predict the students’ performance in the class.